Staying Out: Reentry Protective Factors Among Rural Women Offenders - Staton, Michele (Women & criminal justice, 2019)
The current study examines protective factors for women who transition from county jails to rural Appalachian communities, areas with limited health and behavioral health services. The study included drug-using women recruited from three jails in rural Appalachia and followed-up at 12-months post-release. Analyses focused on differences between women who remained in the community and those who returned to custody, as well as a multivariate model to determine protective factors for reentry success. At the bivariate level, staying out of jail was associated with being older, having a job, not using drugs, stable housing, receiving health treatment, and having prosocial peers. In the multivariate model, the most robust predictors of staying out of jail were drug use abstinence, health care utilization, and prosocial peers. Most research on criminogenic needs associated with reentry success have focused on men, and most focused on reentry to urban communities where services and resources are more accessible. These findings have important implications for criminal justice systems to implement reentry programs for women offenders during the transition to the community.